Intratympanic methylprednisolone injection in idiopathic sudden sensorineural hearing loss after failure of systemic corticosteroid therapy - Ho, Hon Lian; Ruszymah Hj. Idrus,; Lokman Saim,; Aminuddin Saim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Idiopathic sudden sensorineural hearing loss (ISSNHL) is considered to be an otological emergency. The intratympanic (IT) steroid injection technique is introduced to decrease the side effects of systemic steroids and assumed to deliver a higher concentration of corticosteroids into the affected cochlea. The objective of the current study was to evaluate the hearing outcomes of high dose IT methylprednisolone among ISSNHL patients after failure of systemic corticosteroid therapy (SCT). Hearing outcomes of SCT were evaluated over a 15 months period. Upon failure of SCT, the treatment was continued with higher dose IT steroid (methylprednisolone 62.5 mg/mL). Pre-treatment and post-treatment audiometric evaluations were analysed using pure tone audiogram (PTA). There were 36 patients diagnosed with ISSNHL included in the study. After two weeks of SCT, eighteen (56.3%) patients had hearing improvement of more than 10 dB. Another fourteen (43.7%) patients had no hearing improvement (less than 10 dB). Following that, twelve patients were recruited for weekly IT methylprednisolone for three weeks. During the one month follow up after completion of IT therapy, six patients (50%) showed more than 10 dB improvement in the PTA with a mean of 19.37 dB (p<0.05). Out of the six, two patients had more than 20 dB hearing improvement. Almost all patients in this study had an improvement in their symptoms of tinnitus and vertigo. High dose IT methylprednisolone after failure of SCT resulted in significant improvement in the patients’ hearing outcome during one month follow up. The IT therapy not only improved the patients’ hearing but in addition reduced the symptoms of tinnitus and vertigo.